Accessories after the facts: Constraining the timing, duration and conditions of high-temperature metamorphic processes - Taylor, R.; Kirkland, Chris; Clark, Christopher (Elsevier BV, 2016)
© 2016 Elsevier B.V. High-temperature metamorphic rocks are the result of numerous chemical and physical processes that occur during a potentially long-lived thermal evolution. These rocks chart the sequence of events during an orogenic episode including heating, cooling, exhumation and melt interaction, all of which may be interpreted through the elemental and isotopic characteristics of accessory minerals such as zircon, monazite and rutile. Developments in imaging and in situ chemical analysis have resulted in an increasing amount of information being extracted from these accessory phases. The refractory nature of these minerals, combined with both their use as geochronometers and tracers of metamorphic mineral reactions, has made them the focus of many studies of granulite-facies terrains. In such studies the primary aim is often to determine the timing and conditions of the peak of metamorphism, and high-temperature metasedimentary rocks may seem ideal for this purpose. For example pelites typically contain an abundance of accessory minerals in a variety of bulk compositions, are melt-bearing, and may have endured extreme conditions that facilitate diffusion and chemical equilibrium. However complexities arise due to the heterogeneous nature of these rocks on all scales, driven by both the composition of the protolith and metamorphic differentiation. In additional to lithological heterogeneity, the closure temperatures for both radiogenic isotopes and chemical thermometers vary between different accessory minerals. This apparent complexity can be useful as it permits a wide range of temperature and time (T–t) information to be recovered from a single rock sample. In this review we cover: 1) characteristic internal textures of accessory minerals in high temperature rocks; 2) the interpretation of zircon and monazite age data in relation to high temperature processes; 3) rare earth element partitioning; 4) trace element thermometry; 5) the incorporation of accessory mineral growth into thermodynamic modeling; and 6) Hf isotopic signature of zircon overgrowths and its use in linking zircon into major metamorphic phase development.